Maintaining Learner Discipline in Secondary Schools: How School Management Teams Employ Collaborative Strategies to Sustain Learner Discipline - Padayachee, Amy Sarah; Gcelu, Ntombizandile; Makhasane, Sekitla (Research in Social Sciences and Technology- OpenED Network, 2025)
Indiscipline remains a bone of contention in schools across the world. The preponderance of literature associated with indiscipline highlights its severity and the frequency of its manifestation rendering it a global problem. The frequency of indiscipline in the African continent has also made the spotlight in educational research undertaken by various scholars. The literature presents a general conception of the lack of discipline in South African schools. Since the post-dispensation of the education system in South Africa, school management teams have been tasked with managing discipline in schools. Research suggests that school management teams have established, and are currently implementing, strategies to manage learner discipline. Yet, despite the implementation of these strategies, the persistence of indiscipline in schools across South Africa remains a reality. Therefore, strategies need to be used to sustain learner discipline in schools. This study explored collaborative strategies to maintain learner discipline in secondary schools in the ILembe education district. This study is grounded in the Collaborative Leadership Theory. The sample size comprised 24 secondary schools in the ILembe education district. Four participants per school were selected, yielding 96 participants consisting of the principal, one deputy principal, and two departmental heads per school. The participants were selected through simple random sampling. A qualitative research approach was used for this study. The study revealed that collaborative leadership was employed by School Management Teams (SMTs) to lead collaborations in schools to sustain learner discipline. It is recommended that a collaborative leadership approach be adopted to encourage stakeholders to approach all aspects of school management in partnership with stakeholders with a vested interest in the school.